DAMPAK INFLASI, BI RATE, CAPITAL ADEQUACY RATIO (CAR), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO)TERHADAP NONPERFORMING FINANCING (NPF) PADA BANK UMUMSYARIAH DI INDONESIA - RIKA LIDYAH RIKA (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2016)
One of the factors Which can be used to review indicates Banking Crisis Is non-performing financing (NPF), Therefore By analyzing the factors that determine the level of financing problems Anything important and substantial for Financial Stability and the Bank's management.This study aimed to prove the effect of inflation, BI Rate, Capital Adequacy Ratio (CAR), Operating Expenses Operating Income (ROA) against Non Performing Financing (NPF) on Islamic Banks 2010-2014.The sample in this study using purposive sampling method, ie selecting certain characteristics as the key to be sampled, while not included in the defined characteristics are ignored or not sampled. Based on the random sampling method, there were six samples used in this study.Results showed variable partial Inflation does not affect the NPF; Variable BI Rate is partially contained significant positive effect on NPF; Variable CAR partially negatively affect the NPF; Variable BOPO partially contained significant positive effect on NPF; Based on the statistical test F can be inferred that the regression model can be used to determine the effect of inflation, BI Rate, CAR, ROA against NPF together, which means there is a simultaneous effect of inflation, BI Rate, CAR, ROA to NPFKeyword: Inflation BI Rate, CAR, ROA, NPF